2005
DOI: 10.2113/jeeg10.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MASW Data Acquired with a Hydrophone Streamer in a Shallow Marine Environment

Abstract: Seismic shear wave velocity is an important characteristic of sub-bottom materials for geotechnical and environmental characterizations in marine environments. Traditional marine shear wave velocity measurements utilize measurements within borings or data from geophones planted on the bottom. Multichannel Analysis of Surface Waves (MASW) provides a more efficient means to estimate shear wave velocity values of sub-bottom materials using a hydrophone streamer and an airgun seismic source.MASW data were acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…A similar result has been reported by others for both SASW and MASW (e.g. Stokoe et al, 1994, Park et al, 1999and Kaufmann et al, 2005. Independently carried out seismic CPT (SCPT) data, by the University of British Columbia, was also available (Eidsmoen et al, 1985 andLunne et al, 2003a) and these data are also shown in Figure 3(a).…”
Section: Results For Clay Sites Onsoysupporting
confidence: 84%
See 1 more Smart Citation
“…A similar result has been reported by others for both SASW and MASW (e.g. Stokoe et al, 1994, Park et al, 1999and Kaufmann et al, 2005. Independently carried out seismic CPT (SCPT) data, by the University of British Columbia, was also available (Eidsmoen et al, 1985 andLunne et al, 2003a) and these data are also shown in Figure 3(a).…”
Section: Results For Clay Sites Onsoysupporting
confidence: 84%
“…Kaufmann et al (2005) (for shallow marine sediments), Harry et al (2005) (for a fluvial aquifer), Donohue et al (2003Donohue et al ( , 2004) (for very stiff Irish glacial till and very soft clays and silts from Central Ireland respectively) and Park et al (1999) have shown that V s (and hence G max ) can be obtained cheaply and reliably using the Multichannel Analysis of Surface Waves (MASW) method.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of the method include elastic property determination (Donohue et al, 2004 andFoti, 2003), shallow anomaly detection (Park et al, 1998a), bedrock mapping , seismic characterization of pavements Ryden et al, 2001), stratigraphic layer detection (Harry et al, 2005), Poisson's ratio distribution (Ivanov et al, 2000a), and seismic characterization of underwater sediments Ivanov et al, 2000b, Kaufmann et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, successful results have been obtained using surface/Scholte waves to infer the shear-wave properties of the subsurface (Park et al, 1999;Kaufmann et al, 2005;Park et al, 2005). With this approach, surface-wave arrivals are selected, analyzed in terms of their dispersion characteristics, and inverted for a shear-wave model of the shallow subsurface.…”
Section: Introductionmentioning
confidence: 99%